2020
DOI: 10.1111/rec.13260
|View full text |Cite
|
Sign up to set email alerts
|

Selecting native plants for restoration using rapid screening for adaptive traits: methods and outcomes in a Great Basin case study

Abstract: Partnerships between researchers and restoration practitioners can improve restoration outcomes, which is especially important for restoration in challenging settings. Here, we describe one such partnership in the Great Basin, United States, which used trait-based methods and practitioner knowledge to identify the most promising seed sources for restoration. Managers in this region can either use widely available commercial seeds, which are often sourced from far outside the seeding area, or take extra steps t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 37 publications
1
28
0
Order By: Relevance
“…Conversely, a study of two grass species native to the tallgrass prairies of North America ( Sorghastrum nutans and Schizachyrium scoparium ) found that cultivars had larger root systems and used more nitrogen than wild‐collected accessions, while no differences were detected in shoot traits between collection types (Klopf & Baer 2011). Leger et al (2020) showed that wild‐collected seeds had more persistence‐relevant traits, many being root traits such as greater root tips and specific root length than commercially available seeds. Further inquiry into the impacts of plant selection and production practices on root trait values and variation in restoration species and sources is needed, particularly given the important role root traits play in plant establishment and survival (Lloret et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, a study of two grass species native to the tallgrass prairies of North America ( Sorghastrum nutans and Schizachyrium scoparium ) found that cultivars had larger root systems and used more nitrogen than wild‐collected accessions, while no differences were detected in shoot traits between collection types (Klopf & Baer 2011). Leger et al (2020) showed that wild‐collected seeds had more persistence‐relevant traits, many being root traits such as greater root tips and specific root length than commercially available seeds. Further inquiry into the impacts of plant selection and production practices on root trait values and variation in restoration species and sources is needed, particularly given the important role root traits play in plant establishment and survival (Lloret et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The limited accession by drought treatment interactions we observed at the 10-day developmental stage may result from the strong influence of seed provisioning on plant performance during the first days of seedling growth (e.g. Leck et al 2008;Larson et al 2020) or a delay in morphological plant responses to water stress (Sun et al 2020). RMR was the only trait for which an accession by drought interaction was observed at the 10-day developmental stage.…”
Section: Individual Traitsmentioning
confidence: 77%
“…Funk et al 2008;Leger & Baughman 2015). In addition, rapid screening methods have been developed to aid in the identification of promising sources of restoration plant materials (Leger et al 2020). Furthermore, sourcing and production practices aimed at retaining adaptive traits and genetic diversity have recently been refined (Espeland et al 2017;Bucharova et al 2019).…”
Section: Relationships Among Traits and Trait Plasticitymentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, taking into account the analogous evidence from agricultural systems can substantially improve restoration effectiveness. First, although the importance of plant origin has gained increasing attention in restoration ecology (Bischoff et al., 2010; Breed et al., 2019; Leger et al., 2021), the effect of plant seed sourcing location (biotic and abiotic environments) on the interaction of sown plants with soil microbes, including the ability of plants to build and benefit from mycorrhizal interactions in the restored sites, is unclear. For example, Cavender and Knee (2006) demonstrated that the response of a host plant to natural and commercially produced AM fungal inocula strongly depended on the source of seeds used for the experiment.…”
Section: Effects Of Using Commercially Propagated Wildflowers On Plant–fungal Networkmentioning
confidence: 99%